Teaching “fundamental values” in the Swedish education system: Towards an anti-authoritarian Regime of Truth - Piero S. Colla (Quaderni di Sociologia, 2018)
Often lauded for its egalitarian ambitions, over the last 25 years the Swedish education system has undergone a radical shift towards devolved management responsibilities. The article examines this trend by focusing on one of the priorities introduced by recent reforms of the curricula: the need to familiarise students with a set of national “fundamental values”. Obligations and rhetoric linked to this priority, which concerns all areas of teaching, are examined in a long-term perspective and in relation to a feature of the national educational ethos: the refusal to allow any value judgments, which restrict pupil autonomy. The construction of a school of democratic citizenship, which began in the 1940s, has led to a particular system of truth production in which the school claims – first in specific areas such as sexual education, and then more generally – to represent a statistically founded understanding of the “authentic values” of the population. In this area – defined by specific validation procedures in which psychosocial expertise lays down the law – the State is authorised, required even, to exercise directional pressure on the individual conscience.